The occupied [large type] - Parshall, Craig, 1950- (A Trevor Black novel, 2016)
"A story of supernatural suspense. When one of Trevor Black's hometown friends is murdered, the MO is eerily similar to a shocking trail of murders that have already crossed his path. So Trevor must return home to find the killer. . . and face not only his own personal demons, but supernatural ones as well"--